The MAPT gene is differentially methylated in the progressive supranuclear palsy brain. Issue 12 (6th October 2016) - Huin, Vincent; Deramecourt, Vincent; Caparros‐Lefebvre, Dominique; Maurage, Claude‐Alain; Duyckaerts, Charles; Kovari, Eniko; Pasquier, Florence; Buée‐Scherrer, Valérie; Labreuche, Julien; Behal, Hélène; Buée, Luc; Dhaenens, Claire‐Marie; et al.
ABSTRACT: Background: Progressive supranuclear palsy (PSP) is a rare neurodegenerative disease causing parkinsonian symptoms. Altered DNA methylation of the microtubule‐associated protein tau gene correlates with the expression changes in Alzheimer's disease and Parkinson's disease brains. However, few studies examine the sequences beyond the constitutive promoter. Objectives: Because activating different microtubule‐associated protein tau gene control regions via methylation might regulate the differential tau expression constituting the specific signatures of individual tauopathies, we compared methylation of a candidate promoter, intron 0. Methods: We assessed DNA methylation in the brains of patients with different tauopathies (35 Alzheimer's disease, 10 corticobasal degeneration, and 18 PSP) and 19 controls by intron 0 pyrosequencing. We also evaluated methylation in an independent cohort of 11 PSP cases and 12 controls. Frontal (affected by tau pathology) and occipital (unaffected) cortices were analyzed. Results: In the initial samples, one CpG island site in intron 0 (CpG1) showed significant hypomethylation in PSP‐affected frontal cortices when compared with controls ( P  = .022). Such hypomethylation was observed in replicate samples, but not in occipital cortices or other tauopathies. PSP and control samples (combining the initial and replicate samples) remained significantly different after adjustment for potential confounding factors (age, H1/H1 diplotype; P  = .0005). PSP‐affected tissues exhibited microtubule‐associated protein tau RNA hyperexpression when compared with controls ( P  = .004), although no correlation with CpG1 methylation was observed. Conclusions: This exploratory study suggests that regions other than the constitutive promoter may be involved in microtubule‐associated protein tau gene regulation in tauopathies and that intron 0 hypomethylation may be a specific epigenetic signature of PSP. These preliminary findings require confirmation. © 2016 International Parkinson and Movement Disorder Society.